Northrop Frye's Notebooks and Lectures on the Bible and Other Religious Texts. - Frye, Estate of Northrop (Collected Works of Northrop Frye., 2003)
Fully annotated, this latest volume in the Collected Works of Northrop Frye will be an invaluable addition to any literary or religious scholar's library.